Pemanfaatan Singkong Menjadi Keripik bagi Pemuda Desa Tamaran Kecamatan Hinai Kabupaten Langkat - Nanang Putra; Sahril Sandika; Samsul Hakim (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
The aim of the service activity is to use cassava to make chips for the youth of Tamaran Village, Hinai District, Langkat Regency. The methods used in service activities include: 1) the service implementation team together with partners invites the entire community at a deliberation at the Tamaran Village Office to be more creative in processing cassava into chips which are then given the name "Lucky Cassava Chips"; 2) This business must have a minimum of 20 members, because producing cassava chips to meet customer demand requires extra effort from all members. The business led by Mr. Afandin is the first founder and has experience processing and producing cassava chips, so that the youth of Tamaran Village have entrepreneurial experience and have home jobs; and 3) the business of processing cassava into chips will continue and will even be improved into better packaging or design because currently partners produce cassava chips once a week which takes 2-3 days to complete. Partners buy cassava from farmers on Saturday afternoons and produce it on Sunday mornings, then package it in the evening. This has become a routine activity every week. The service implementation activity lasted for 3 days, from 1 - 3 July 2023. The service implementation team carried out activities to make cassava chips in Tamaran Village, which was followed by mentoring activities.